The Developmental Periods of Mass Media from the Central Region, to the Northeast Region and to the Thai-So Ethnic Group of Kusuman District - and Sekson Yongvanit, Benjapa Kaithong (Journal of Community Development Research (Humanities and Social Sciences); Vol 9 No 1 (2559): January - April 2016, 2016)
The objective of this article is to study the developmental periods of mass media from the central region, to the northeast region and to the Thai-So community of Kusuman district. Purposive sampling technique was used for selecting 35 key informants. The research instrument was semi-structured interview. All raw materials were analyzed by content analysis. The research findings revealed that not only was the developmental periods of mass media from the central region, to the northeast region, and to the Thai-So community of Kusuman district at different times, but was also influenced by various driving forces. Moreover, the time scales of mass media development from the central to the northeast region and from the northeast region to the Thai-So community of Kusuman district were likely to continue to be reduced. Namely, the journey time of newspaper from the central region to the northeast region was around 116 years, followed by radio in around 10 years, television 7 years, internet 6 years, and satellite television 5 years. Similarly, the journey time of newspaper from the northeast region to the Thai-So community of Kusuman district was around 14 years, followed by television and internet in around 8 years, radio 7 years and satellite television 6 years. Therefore, this research predicts that, in the digital age, new forms of digital media-such as smart phones, tablets, Google glasses, smart watches and so forth - will become more rapidly proliferated into the northeast region and the Thai-So community of Kusuman district until there will be no difference between their arrival times. More Interestingly, all types of mass media - including newspaper, radio, television, satellite television and Internet - were available within the Thai-So community of Kusuman district but the Thai-So people are likely to be exposed to radio and television to a greater extent than other media. It was fair to say that they are likely to access mass media that requires no skills.   Keywords:   The Developmental Periods of Mass Media, The Central Region, The Northeast Region, The Thai-So Community of Kusuman District, Media Exposure
Keywords: The Developmental Periods of Mass Media, The Central Region, The Northeast Region, The Thai-So Community of Kusuman District, Media Exposure